Effects of Drug Abuse on Primary Education: An Overview Context - Sarkingobir, Yusuf; Tukur, Ummu (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
The focused aim of this paper is to utilize review/concept methods of research to elucidate drug abuse and its effects on education. The paper, therefore, explains drug abuse under the following: Negative effects on academic performance, elicitation of malnutrition, instigation of ill-health, causing absenteeism, factors increasing drug abuse, features of drug abusers, theories, causes, effects, and prevention. Indeed, drug abuse education in many ways, to save many of our youngsters interventions are needed. The research methodology employed a systematic literature review approach, which involved identifying, selecting, and analyzing relevant academic sources pertaining to the impact of drug abuse on school children. The initial step included searching of various databases such as PubMed, Google Scholar, and academic library catalogs using keywords related to drug abuse, elementary education, and child development. Following the search process, articles were screened based on inclusion criteria, including publication date, relevance to the research topic, and methodological rigor. Subsequently, the selected literature was synthesized to identify common themes, patterns, and findings regarding the adverse effects of drug abuse on academic performance, social behavior, and overall well-being among elementary school students. The results of the literature review underscored the urgent need for targeted prevention and intervention strategies to address the multifaceted challenges posed by drug abuse in elementary school settings.